Case Report: Pathological Personality Traits Through the Lens of the ICD-11 Trait Qualifiers and the DSM-5 Section III Trait Model: Two Patients Illustrating the Clinical Utility of a Combined View - Bastiaens, Tim; Smits, Dirk; Claes, Laurence (Frontiers in Psychiatry, 2021)
We report on two patient cases as part of everyday clinical practice, comparing their pathological personality traits through the lens of the ICD-11 trait qualifiers and the DSM-5 Section III personality trait model. We compare higher order pathological personality domains and lower order pathological personality trait facets of patient MAMI (diagnosed with borderline personality traits according to DSM-5 Section II), and patient LABU (diagnosed with obsessive-compulsive personality traits according to DSM-5 Section II) with normative data and with each other. Findings highlight the clinical utility of a ICD-11/DSM-5 combined view, including: (1) the Disinhibition/Anankastia personality domain distinction as advocated in the ICD-11 model, (2) the Psychoticism personality domain as conceptualized in the DSM-5 Section III personality trait model, as well as (3) the use of lower order personality trait facets within each higher order personality domain.